EVALUATION OF THE VIRUS-ANTIBODY COMPLEX VACCINE ADMINISTERED IN OVO VERSUS A TRADITIONAL PROGRAMME AGAINST THE INFECTIOUS BURSAL DISEASE UNDER FIELD CONDITIONS IN BROILERS - Paredes V., Carmen (2009)
A new vaccination programme against infectious bursal disease using a virusantibody complex vaccine in comparison with a traditional programme under field conditions was evaluated. In each group, 21,800 broiler chickens of Cobb Vantress 500 line were used. The experimental group was vaccinated with the strain 2512 in combination with specific antibodies at the incubation plant on day 18 of embryonic development, whereas the control group received two vaccines of live virus, the Bursine®2 and Bursa Blen, administered by drinking water at 8 and 19 days of age respectively. Body weight, feed conversion index, European Production Efficiency Index, mortality, bursal index, histopathological lesions, and antibody levels against IBDV were evaluated. Birds of the experimental group showed higher body weight (p<0.05), and better feed conversion index and production efficiency index at 47 days of age than the control group. Both groups showed bursal atrophy from 35 days of age onwards, however, the histopathological results only showed moderate lesions of atrophy and lymphoid depletion in bursas in both groups during those periods. Antibody titers were higher at 35 and 42 days of age in the experimental group and at 47 days in the control group (p<0.05). Both vaccination programmes produced lesions of variable degree in bursas, nevertheless, birds that received the vaccine complex virus antibody had a better productive performance.